Acid-triggered core cross-linked nanomicelles for targeted drug delivery and magnetic resonance imaging in liver cancer cells - Li X (Dove Medical Press, 2013)
Xian Li,1,* Hao Li,2,4,* Wei Yi,3 Jianyu Chen,1 Biling Liang1 1Radiology Department, The Sun Yat-Sen Memorial Hospital, Sun Yat-Sen University, Guangzhou, People's Republic of China; 2Center of Biomedical Engineering, School of Chemistry and Chemical Engineering, Sun Yat-Sen University, Guangzhou, People's Republic of China; 3Radiotherapy Department, The First Affiliated Hospital, Guangzhou Medical University, Guangzhou, People's Republic of China; 4School of Engineering, Sun Yat-Sen University, Guangzhou, People's Republic of China *These authors contributed equally to this work Purpose: To research the acid-triggered core cross-linked folate-poly(ethylene glycol)-b-poly[N-(N',N'-diisopropylaminoethyl) glutamine] (folated-PEG-P[GA-DIP]) amphiphilic block copolymer for targeted drug delivery and magnetic resonance imaging (MRI) in liver cancer cells. Methods: As an appropriate receptor of protons, the N,N-diisopropyl tertiary amine group (DIP) was chosen to conjugate with the side carboxyl groups of poly(ethylene glycol)-b-poly (L-glutamic acid) to obtain PEG-P(GA-DIP) amphiphilic block copolymers. By ultrasonic emulsification, PEG-P(GA-DIP) could be self-assembled to form nanosized micelles loading doxorubicin (DOX) and superparamagnetic iron oxide nanoparticles (SPIONs) in aqueous solution. When PEG-P(GA-DIP) nanomicelles were combined with folic acid, the targeted effect of folated-PEG-P(GA-DIP) nanomicelles was evident in the fluorescence and MRI results. Results: To further increase the loading efficiency and the cell-uptake of encapsulated drugs (DOX and SPIONs), DIP (pKa≈6.3) groups were linked with ~50% of the side carboxyl groups of poly(L-glutamic acid) (PGA), to generate the core cross-linking under neutral or weakly acidic conditions. Under the acidic condition (eg, endosome/lysosome), the carboxyl groups were neutralized to facilitate disassembly of the P(GA-DIP) blocks' cross-linking, for duly accelerating the encapsulated drug release. Combined with the tumor-targeting effect of folic acid, specific drug delivery to the liver cancer cells and MRI diagnosis of these cells were greatly enhanced. Conclusion: Acid-triggered and folate-decorated nanomicelles encapsulating SPIONs and DOX, facilitate the targeted MRI diagnosis and therapeutic effects in tumors. Keywords: acid-triggered, DOX, nanomicelle carrier, folate-targeted effect, SPIONs